Implementasi Perhitungan Harga Pokok Produksi Bagi Pelaku Usaha Kuliner Desa Pariwisata - Ayu Rakhma Wuryandini; Siti Pratiwi Husain (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity was organized by a team of lecturers from the Department of S1 Accounting, Gorontalo State University in 2024 in Botutunuo Village, Kabila Bone District, Bone Bolango Regency, Gorontalo Province as a form of implementation of the Tri Dharma of Higher Education. This coastal village, which is located in the Tomini Bay area and has tourism potential, faces obstacles in the management of culinary businesses owned by the local community. The main problem of partners is low professionalism in business management and suboptimal bookkeeping administration. This activity aims to increase the knowledge and ability of MSME actors in implementing cost accounting for controlling and reporting production costs. The program is carried out in four stages: location survey, material socialization, technical assistance in calculating the cost of production, and monitoring and evaluation of implementation results. The results of the service showed that 75% of the participants understood the material well and welcomed the sustainability of the mentoring. This activity makes a positive contribution to improving the competence of culinary business actors in coastal tourism areas through the application of cost accounting.